Ultrastructural Evidence of Synapse Preservation and Axonal Regeneration Following Spinal Root Repair with Fibrin Biopolymer and Therapy with Dimethyl Fumarate - Kempe, Paula Regina Gelinski; de Castro, Mateus Vidigal; Khuriyeh, Victor Campos; Barraviera, Benedito [UNESP]; Ferreira, Rui Seabra [UNESP]; de Oliveira, Alexandre Leite Rodrigues (My University, 2023)
Spinal cord injury causes critical loss in motor and sensory function. Ventral root avulsion is an experimental model in which there is the tearing of the ventral (motor) roots from the surface of the spinal cord, resulting in several morphological changes, including motoneuron degeneration and local spinal cord circuitry rearrangements. Therefore, our goal was to test the combination of surgical repair of lesioned roots with a fibrin biopolymer and the pharmacological treatment with dimethyl fumarate, an immunomodulatory drug. Thus, adult female Lewis rats were subjected to unilateral ventral root avulsion of L4–L6 roots followed by repair with fibrin biopolymer and daily treatment with dimethyl fumarate (15 mg/Kg; gavage) for 4 weeks, the survival time post-surgery being 12 weeks; n = 5/group/technique. Treatments were evaluated by immunofluorescence and transmission electron microscopy, morphometry of the sciatic nerve, and motor function recovery. Our results indicate that the combination between fibrin biopolymer and dimethyl fumarate is neuroprotective since most of the synapses apposed to alfa motoneurons were preserved in clusters. Also, nerve sprouting occurred, and the restoration of the ‘g’ ratio and large axon diameter was achieved with the combined treatment. Such parameters were combined with up to 50% of gait recovery, observed by the walking track test. Altogether, our results indicate that combining root restoration with fibrin biopolymer and dimethyl fumarate administration can enhance motoneuron survival and regeneration after proximal lesions.
Keywords: avulsion; fibrin biopolymer; motoneuron; spinal cord; synapse